A linguagem do cárcere: um mapeamento linguístico da penitenciária feminina de Foz do Iguaçu - Palma, Adriane Dequi (2024)
Through language, individuals express the identity of the group to which they belong. Within the penitentiary system, composed by a minority group excluded from society, distinct linguistic resources from the standard norm of the Portuguese language are used. This instigate us to research into their social relevance within this system. Thus, this dissertation aims to observe and analyze the lexicon of the prison environment at the Women's Penitentiary of Foz do Iguaçu - Progression Unit. So, our question is: how is the linguistic variety, at the lexical level, presented within the community of the Foz do Iguaçu Penitentiary? From this question, the following objectives emerged: - general objective: to map the lexical variation of the speech within the community of the Foz do Iguaçu Penitentiary – Progression Unit; - specific objectives: i) to analyze and describe the lexicon of the speech within the community of the Women's Penitentiary of Foz do Iguaçu – Progression Unit; ii) to develop a linguistic (diastratic) map of the community of the Women's Penitentiary of Foz do Iguaçu. To guide the study, we chose the theoretical-methodological model of Variationist Sociolinguistics (Labov 2008), with a qualitative approach. For data generation, we used observation and semi-structured interviews. The results of this research seek to expand studies related to this social group, with the aim of seeking improvements in the intramural relationships among all individuals involved in the penal unit. Furthermore, it encourages teachers to reflect on prison vocabulary and to break the paradigms surrounding the existing linguistic variations in this environment.